Twelve myths of religion and psychiatry: Lessons for training psychiatrists in spiritually sensitive treatments - Coyle, Brent R. (Mental health, religion & culture, 2001)
Our world is filled with renewed interest in spiritual dimensions. Educators and clinicians, however, have little practical guidance for these complex issues. The American Council on Graduate Medical Education's Residency Review Committee Guidelines now require training of resident physicians in spiritual sensitivity. The current level of sophistication and rapid expansion of this powerful and complex dynamic of the profession are a challenge to psychiatrists. Problems now facing many training programmes are lack of data, negative bias and misinformation surrounding spirituality. This paper focuses on 12 common myths often associated with the interface of psychiatry and spirituality.